Crescentic Glomerulonephritis with Anti-GBM and p-ANCA Antibodies - Tariq Javed; Parag Vohra (Case Reports in Nephrology)
We are presenting a case of renal failure with anti-GBM and p-ANCA antibodies positive. Patients with dual antibodies are considered to be a vasculitis-variant of anti-GBM antibody nephritis. These patients may have atypical presentation and it may delay diagnosis and treatment. Recurrence rate is higher in these patients. We reviewed the literature of cases and studies on cresenteric glomerulonephritis with anti-GBM and p-ANCA positive patients. We recommend that patients suspected with pulmonary-renal syndrome should be checked for anti-GBM and p-ANCA antibodies, should undergo renal biopsy and should should have close long term follow up to watch for recurrence.